Access to health and rehabilitation services for persons with disabilities in Sierra Leone - focus group discussions with stakeholders - Lina Magnusson; Ismaila Kebbie; Victoria Jerwanska (BMC, 2022)
Abstract Background In Sierra Leone persons with disabilities are at higher risk of living in poverty and have poor access to a fragile healthcare and rehabilitation services. The aim was to explore stakeholders' perceptions of access to health and rehabilitation services for persons with disabilities in Sierra Leone. Methods Seven focus group discussions, including stakeholders working within the field of disability was conducted. Results The subthemes were: continuous stigmatisation of persons with disabilities throughout life; long distances and transportation issues to access health and rehabilitation facilities; financial constraints; infrastructural barriers to healthcare and rehabilitation services and healthcare personnel's negative attitudes and inadequate knowledge towards persons with disabilities; rehabilitation and healthcare facilities lacking materials to provide quality services; lack of specialised services and rehabilitation personnel for complex rehabilitation and the need for continuous education of new and current rehabilitation personnel. Conclusion Local actors need to take charge and renew efforts made by international organisations by providing trained rehabilitation staff and quality rehabilitation services. Rehabilitation services need to be affordable and transportation costs covered for persons with disabilities to access healthcare and rehabilitation services. Continuous education of the public and health personnel about disability is necessary to reduce negative attitudes towards persons with disabilities.